The physical oceanographic processes on the southeast African shelf and slope - Russo, Cristina Serena (Department of Oceanography, 2019)
Situated between the southeast coast of South Africa and the western edge of the Agulhas Current, is the southeast African shelf. The Agulhas Current, like other western boundary currents of the world, strongly influences the oceanographic conditions of its adjacent shelf system. Limited societal drivers have resulted in the southeast African shelf being one of the least studied and under-sampled shelf systems in southern Africa. The in situ sample deficit has led to the majority of studies conducted in this region to be carried out using satellite data and modelling. In order to identify the physical oceanographic processes occurring on the southeast African shelf and slope, as well as the influence that the Agulhas Current has on them, this study analysed satellite data combined with high resolution in situ data, acquired during two hydrographic surveys of the southeast African shelf and slope, during January/February (austral summer) and July/August (austral winter) 2017. The Agulhas Current as well as a number of physical processes were observed to influence the shelf region. The snapshot of the two seasons given by the January/February and July/August in situ data presented indications of seasonality of temperature and salinity within the upper water masses but not within the deeper water masses. The same five water masses, Tropical Surface Water (TSW), Subtropical Surface Water (STSW), South Indian Central Water (SICW), Red Sea Water (RSW) as well as Antarctic Intermediate Water (AAIW), were observed during each cruise. As a result of the westward widening shelf from just east of East London, divergence-induced upwelling was observed between the coast and the inshore edge of the Agulhas Current, during both January/February and July/August. Ekman veering in the bottom boundary layer was observed between Port Alfred and East London during January/February as a result of the close proximity of the Agulhas Current to the slope. Altimetry data indicated the presence of a cyclonic eddy during both the January/February and July/August 2017 surveys. The presence of cold nutrient-rich SICW in the bottom layers on the shelf during January/February and July/August was as a result of the uplift caused by Ekman pumping associated with the cyclonic eddies. AAIW, usually observed along the offshore edge of the Agulhas Current, was found on the slope along the inshore edge of the Agulhas Current, as a result of the presence of cyclonic eddies. Wind-driven upwelling, induced by offshore Ekman transport and vertical mixing, resulted in the surfacing of cooler waters from below at several locations. Chlorophyll-a concentrations were found to be higher during January/February than during July/August 2017. The dissolved oxygen levels observed on the shelf during both surveys were found to be in the range where the biological responses would be insignificant, suggesting that oxygen availability, on the southeast African shelf, adequately facilitates the survival of the existing shelf biology and that low oxygen conditions do not seem to impact the shelf. This study provides the description of the first high resolution shelf wide hydrographic surveys of the region, during the austral summer and winter (even though they are considered as snapshots) which sets a baseline of oceanographic conditions on the shelf as well as the processes affecting it. The results of this study can be used by the scientific community and governmental departments to better implement conservation regulations regarding marine protected areas in the region.